INFLUENCE OF STRESS ON SECONDARY METABOLITES PRODUCTION FROM CALLUS OF MORINGA OLEIFERA IN VITRO - & Ameen, Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was conducted to study the effect of sucrose, poly ethylene glycol (PEG) on hypocotyl induced callus of Moringa oleifera at the plant tissue culture lab.- College of Agriculture– University of Baghdad from February 2015 to May 2016. Sucrose concentrations were 30, 60, and 90, 120 g .L -1 and PEG 0, 25, 50 and 100 g .L -1 added to MS medium supplemented with 2.0 mg .L -1 of 2, 4-D and 0.1 mg .L -1 of NAA. MS medium supplemented with120 g .L -1 of sucrose gave the best amount of Zeatin, Quercetin and Kaempferol reached to 103.4, 1324.6 and 966.5 µg. g dry weight of callus-1 respectively. The concentrations of active compound increasing with adding PEG, MS medium supplemented with 100 g .L -1 PEG gave the highest value of Zeatin, Quercetin and Kaempferol which recorded 92.01, 3528.0 and 931.0 µg. g dry weight of callus-1 respectively. We found that we could increase the production of active material from callus that induced from explant by exposure the callus to several stress and then could separate the pure active material and used it as a drug in medicine.